2017
DOI: 10.4236/ojepi.2017.72008
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Eating Disorders and Stress among Medical Undergraduate: A Cross-Sectional Study

Abstract: Introduction: Eating disorders are compulsive behaviours that can consume a person's life to the point of becoming life threatening. Medical college can be a very stressful time and previous studies had found that stress could be a main factor leading to higher risk of eating disorder. We aimed to determine the association between stress and eating disorders among undergraduate medical students. Methods: A cross-sectional study was conducted among 320 respondents comprises of Year 3, 4 and 5 medical students i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 21 publications
3
22
2
Order By: Relevance
“…In a specific, general life stressors over all can be a very good predictor of eating disorder and more specific "Binge eating" among students. This finding is not in agreement with the study of Ngan [28]. The logical explanation to this finding can be viewed as students release there stress and tensions toward foods and into eating as a way to cope with their stressful life and demanding issues.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…In a specific, general life stressors over all can be a very good predictor of eating disorder and more specific "Binge eating" among students. This finding is not in agreement with the study of Ngan [28]. The logical explanation to this finding can be viewed as students release there stress and tensions toward foods and into eating as a way to cope with their stressful life and demanding issues.…”
Section: Discussioncontrasting
confidence: 92%
“…The sample consisted of (263) who took Cohen Perceived Stress Scale to determine the association between stress and eating disorders among undergraduate students. The result indicated that students experienced moderate stressful life; however the result indicated no significant relationship between stress and risk of eating disorder, and no significant relationship between age, gender, residence, and risk of developing eating disorder among students [28].…”
Section: Other Typical Eating Disordersmentioning
confidence: 82%
See 3 more Smart Citations